Vibration Response Prediction of Plate with Particle Dampers Using Cosimulation Method - Dongqiang Wang; Chengjun Wu (Shock and Vibration)
The particle damping technology is a passive vibration control technique. The particle dampers (PDs) as one of the passive damping devices has found wide use in the field of aeronautical engineering, mechanical engineering, and civil engineering because it has several advantages compared with the forms of viscous damping, for example, structure simplicity, low cost, robust properties, and being effective over a wide range of frequencies. In this paper, a novelty simulation method based on multiphase flow theory (MFT) is developed to evaluate the particle damping characteristics using FEM combining DEM with COMSOL Multiphysics. First, the effects of the collisions and friction between the particles are interpreted as an equivalent nonlinear viscous damping based on MFT of gas particle. Next, the contribution of PDs is estimated as equivalent spring-damper system. Then a cantilever rectangular plate treated with PDs is introduced in a finite element model of structure system. Finally frequency response functions (FRFs) of the plate without and with particle dampers are predicted to study characteristics of the particle damping plates under forced vibration. Meanwhile, an experimental verification is performed. Simulation results are in good agreement with experiment date. It is concluded that the simulation method in this paper is valid.